How do you find the antiderivative of #(1 + e^(2x)) ^(1/2)#?

Answer 1

# 1/2ln|(1-sqrt(1+e^(2x)))/(1+sqrt(1+e^(2x)))|+sqrt(1+e^(2x))+C.#

Let us subst. #e^x=tany rArr e^xdx=sec^2ydy, or, dx=sec^2y/e^x*dy=sec^2y/tany*dy=1/(cosysiny)dy#
#:. I=intsqrt(1+e^(2x))dx#
#=int{sqrt(1+tan^2y)/(cosysiny)}dy,#
#=int1/(cos^2ysiny)dy=int{(siny)/(cos^2ysin^2y)}dy.#
Hence, #cosy=t rArr -sinydy=dt, and, :.,#
#I=-int1/{t^2(1-t^2)}dt,#
#=int1/{t^2(t^2-1)}dt=int[{t^2-(t^2-1)}/{t^2(t^2-1)}]dt,#
#=int[t^2/{t^2(t^2-1)}-(t^2-1)/{t^2(t^2-1)}]dt,#
#=int(1/(t^2-1)-1/t^2)dt,#
#=1/2ln|(t-1)/(t+1)|+1/t,#
#=1/2ln|(cosy-1)/(cosy+1)|+1/cosy,#
#=1/2ln|(1-secy)/(1+secy)|+secy.#
Since, #tany=e^x rArr secy=sqrt(1+tan^2y)=sqrt(1+e^(2x)),# we get,
#I=1/2ln|(1-sqrt(1+e^(2x)))/(1+sqrt(1+e^(2x)))|+sqrt(1+e^(2x))+C.#

Enjoy Maths.!

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

To find the antiderivative of ( (1 + e^{2x})^{1/2} ), we can use the substitution method. Let's denote ( u = 1 + e^{2x} ). Then, ( du/dx = 2e^{2x} ), and ( dx = \frac{1}{2e^{2x}} du ).

Now, substitute ( u ) and ( dx ) into the integral:

[ \int (1 + e^{2x})^{1/2} dx = \int u^{1/2} \frac{1}{2e^{2x}} du ]

Simplify the integral:

[ \frac{1}{2} \int \frac{u^{1/2}}{e^{2x}} du ]

Now, ( e^{2x} = u - 1 ), so:

[ dx = \frac{1}{2(u - 1)} du ]

Substitute ( dx ) into the integral:

[ \frac{1}{2} \int \frac{u^{1/2}}{u - 1} du ]

Now, perform partial fraction decomposition:

[ \frac{u^{1/2}}{u - 1} = \frac{A}{u - 1} + \frac{B}{\sqrt{u}} ]

After solving for ( A ) and ( B ), integrate each term separately:

[ \frac{1}{2} \int \left( \frac{A}{u - 1} + \frac{B}{\sqrt{u}} \right) du ]

[ = \frac{A}{2} \int \frac{1}{u - 1} du + \frac{B}{2} \int \frac{1}{\sqrt{u}} du ]

[ = \frac{A}{2} \ln|u - 1| + \frac{B}{2} \cdot 2\sqrt{u} + C ]

Substitute ( u = 1 + e^{2x} ) back into the expression:

[ = \frac{A}{2} \ln|1 + e^{2x} - 1| + B\sqrt{1 + e^{2x}} + C ]

[ = \frac{A}{2} \ln|e^{2x}| + B\sqrt{1 + e^{2x}} + C ]

[ = Ax + B\sqrt{1 + e^{2x}} + C ]

This is the antiderivative of ( (1 + e^{2x})^{1/2} ), where ( A ) and ( B ) are constants and ( C ) is the constant of integration.

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7